Development of Syncretic Mystical Christianity in China - A resultant of its spread by the Silk Road:-A brief comparative overview of the pattern of evangelization, the cross- influences and the result - Johns, J. (The International Conference on Land Transportation, Locomotive Heritage and Road Culture - 2017, 2017)
The Silk Road which passed through Central Asia to the East- linked the West with regions like India and China, facilitating the trade of silk and other commodities like horses and tea, but as a by-product, exchange of ideas and culture too was also facilitated. As a result of various factors, Nestorian Christianity began to spread to the East, one of the routes taken was the Silk Road- thus helping Christianity to reach China during the Tang Dynasty (618-907 AD).This Christianity had already been influenced by Greek culture and Syriac culture, and on its way to China got influenced by Zoroastrian culture- the influences were part of the syncretic culture of the caravan Silk Road. At its destination, China- Christianity was met with Indian Culture, Buddhist Culture (Mystical- Vajrayana Buddhism) and Chinese Culture- the result here again was an amalgamation of all of these cultures leading to the development of syncretic Christianity and literature which has a clear Buddhist and Mystical touch to it. Through this paper the researcher will examine the various art-archaeological evidences like the Nestorian Stele at Xian and literature called the Jesus Sutras like “the Sutra on the Origin of Origins”, “Da Qin Hymn to the Transfiguration of the Great Holy One” etc. Along with previous research done in this area. An attempt has also been made to study the pattern of evangelization on the Silk Road, segregation of the influences by the land route and other routes, the result and further cross -influences that this Syncretic Mystical Christianity had on other areas.
Keywords: Christianity; China; Silk Road; Mystical; Syncretic; Culture